التكنولوجيا ومناهج تعليم العربية: دراسة في الجامعات الإسلامية والعالمية - Shair Ali Khan; Dr. Nazir Ahmad (التراث الأدبي)
Education and technology have increasingly converged, especially in the context of teaching languages. Arabic, as one of the most significant global languages, has witnessed an array of technological advancements in its teaching methodologies. This study explores various online platforms and tools used to teach Arabic in Islamic and global universities. It highlights the increasing reliance on technology in modern educational systems, focusing on how these innovations have simplified teaching methodologies and expanded access to Arabic language learning.